Marketig Of Rubber By Small Growers In Nedumangad Taluk - Abdul Rasheed M (Department of Plantation Crops and Spices, College of Horticulture, 1996)
The study “Marketing of rubber by small growers in Nedumangad taluk” revealed that a major portion of the sheet rubber produced by the small holders is of inferior quality. It is a fact of differential pricing based on quality of sheets is not in vogue in the locality where the study was conducted . For the production of better quality grades , the existing facilities for processing as well as infrastructure should be further developed.With regard to the system of tapping adopted , it was observed that majority of the growers adopted daily tapping and not bothered about the ill effects due to daily extraction . Albeit, the beneficial effects of scientific processing of sheet rubber is well established , it is paradoxical to note that majority of the farmers are not aware/following scientific aspects of processing like use of correct concentration of acid , sodium bi sulphate, paranitrophenol, sieving, smoking etc. for the production of sheet. The reason for this anomaly is clearly understood that there is no marked variation in prices of quality and ungraded sheet rubber. However, an interesting factor to be noted in this aspect is that the difference between the farmgate price and terminal market price is negligible as the producers received more than 80 percent of the price paid by the consumer